100 Exercices for a Choreographer and Other Survivors - Lilja, Efva (Sweden Ellerströms, 2012)
In this book Efva Lilja shares 100 exercises in the art of survival. They are based on her experience from many years as dancer and choreographer, but can be used by all. Both poetical and practical, they teach how to be present in in your body, how to make time your home and, simply, how to live. Efva Lilja is a powerful and singular voice in the world of the contemporary arts. All her work bears a deeply personal stamp and its highly individual aesthetic underpins a true poetics of dance. A compelling sense of the dramatic and a marvellous feeling for form allow her to show us the way to an entirely new experience of what is remarkable and strange about human life.A highly developed way working helps with the breaking of new ground. Her work is penetrating, surprising and astonishes people by confronting them with a totally new experience of what dance can be. It is beautiful, ugly, at times inflammatory and very enjoyable. Seeing her work is a thought-provoking experience as the audience encounters what are frequently unforgettable images and events: in performances, films, drawings as well as in her texts.It was with a background as a dancer that Efva Lilja started to work as a choreographer and she presented her first work in 1982. Since then she has produced work for various stage settings, site specific performances, film and television. Some of her most celebrated work has been produced as commissions from major art institutions such as the Centre Georges Pompidou in Paris in 1994, Stockholm's Moderna Museet in 2000 and 2003, the Baltic Art Centre in Visby 2001 and the Guggenheim Museum in Bilbao in the same year. Efva Lilja has conducted artistic research projects and she has written several notable books about dance.In the course of the years, Efva Lilja has received a number of major prizes and awards for her artistic work. In 2003, she was appointed Professor of Choreography and in 2006 she became the Vice Chancellor of The University of Dance and Circus in Stockholm.